Role of membrane lipid peroxidation, enzymatic and non-enzymatic antioxidative systems in the development of chilling injury in Japanese plums - Singh, Sukhvinder; Singh, Zora (American Society for Horticultural Science, 2012)
Chilling injury (CI) is a major postharvest constraint in the long-term cold storage, transportation, and distribution of japanese plums (Prunus salicina). The aim of the work was to explain the development and severity of CI in japanese plums based on the oxidative stress theory following time course analysis of enzymatic and nonenzymatic antioxidants. Changes in membrane lipid peroxidation and enzymatic and non-enzymatic antioxidative systems in japanese plum cultivar Blackamber were determined at weekly intervals during 5 weeks of cold storage at 0 8C and at 2-day intervals during poststorage simulated shelf conditions (21 ± 1 8C) for 8 days after each week of cold storage. Fruit respiration and ethylene production rates showed typical climacteric patterns after removal from cold storage and these rates were relatively high after 4 and 5 weeks compared with 0 to 3 weeks of storage. The CI symptoms first appeared after 3 weeks of cold storage after fruit had been transferred to simulated shelf conditions.The incidence and severity of CI intensified with increasing storage duration. The extent of lipid peroxidation indicated by concentration of thiobarbituric acid-reactive substances and membrane damage manifested as electrolyte leakage increased with increasing duration of storage and subsequent simulated shelf conditions. Membrane lipid peroxidation exhibited positive correlation with the severity of CI. Activities of primary antioxidant enzymes and the enzymes involved in the ascorbate–glutathione cycle were determined to explain the levels of reduced and oxidized forms of cellular redox buffers, ascorbate and glutathione. In response to chilling stress, antioxidative protection systems operated efficiently during the first 3 weeks of cold storage, but extended storage resulted in loss of ability to ameliorate increasing levels of oxidative stress. In this study, the comprehensive analyses of various metabolites and antioxidative systems explain the series of events involved in development of CI in japanese plums in support of the oxidative stress theory.